Os principais indicadores econômico-financeiros que contribuem com a avaliação do momento para pedir a recuperação judicial - Ribeiro, Carlos Alexandre Capistrano (2022)
The solvency models established in the literature by Kanitz (1974, 1976, 1978), Elizabetsky (1976) and Matias (1978) inspired this study to build a solvency model based on economic and financial indicators that could contribute to the prediction of the financial situation and solvency of companies in the real estate development segment. Therefore, this dissertation aims to demonstrate the importance of management and its accounting and financial records to ensure assertiveness in preparing economic and financial indicators that can demonstrate, through statistical and mathematical models, whether the company is signaling the moment to seek judicial reorganization. The old Law No. 7661 of 1945 Bankruptcy and Reorganization, tied to high inflation, canceled the debts with the creditors; it was, thus, not well seen by the market. The new Judicial Reorganization and Bankruptcy Law No. 11,101 of 2005, and the current Law No. 14,112 of 2020, brought major and important changes for the recovery of the company, for overcoming its financial situation, and for society at large, generating the maintenance of jobs as a productive source. The real estate development segment is one of the biggest drivers of the economy and job generation. Although there are thousands of companies from small to large in this segment, this study was limited to publicly traded companies listed on the B3 Brazilian Stock Exchange in order to guarantee data equity. We analyzed 28 companies in the segment, of which two were classified as being in receivership and 26 as solvent. Through the multivariate statistical model and the discriminate analysis technique, it was possible to classify qualitative and quantitative data as indicators extracted from Economatica, a secondary data source. With the help of the IBM® SPSS® statistical software, version 26, a friendly and intuitive tool, a model was obtained that can not only help predict whether the company is on the verge of applying for judicial reorganization but also provide an opportunity to improve the model developed in this study